2017
DOI: 10.1186/s40543-017-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-irradiated green synthesis of gold nanoparticles for catalytic and anti-bacterial activity

Abstract: Background: Herein, we report a green, microwave irradiated synthesis of gold nanoparticles by using a simple, low cost and ecofriendly technique. The green technique has been developed for the synthesis of gold nanoparticles (AuNPs) from HAuCl 4 using papaya leaf extract. The papaya leaf extract served both as a reductant and a stabilizer. Method: The synthesized AuNPs had been characterized by UV-Visible spectrophotometer, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Zeta potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…For example, the spectrum of gPdNPs has a peak at 390 nm (Figure 1), which is specific for PdNPs [18,61]. A peak of gAuNPs in the range 525-590 nm is specific for chemically-synthesized AuNPs of different sizes, according to data reported in the literature [8,12,13,19,38,42,43,48] as well as our results [56,62]. The color, size and shape of AuNPs and gAuNPs are dependent on the NPs' synthesis conditions: culture liquid of a 1-day culture incubated for 3 days with HAuCl 4 produces a dark blue solution of small gAuNPs with a peak at 525 nm.…”
Section: Characterization Of the Green-synthesized Nanoparticlessupporting
confidence: 57%
See 1 more Smart Citation
“…For example, the spectrum of gPdNPs has a peak at 390 nm (Figure 1), which is specific for PdNPs [18,61]. A peak of gAuNPs in the range 525-590 nm is specific for chemically-synthesized AuNPs of different sizes, according to data reported in the literature [8,12,13,19,38,42,43,48] as well as our results [56,62]. The color, size and shape of AuNPs and gAuNPs are dependent on the NPs' synthesis conditions: culture liquid of a 1-day culture incubated for 3 days with HAuCl 4 produces a dark blue solution of small gAuNPs with a peak at 525 nm.…”
Section: Characterization Of the Green-synthesized Nanoparticlessupporting
confidence: 57%
“…NPs of noble metals possess low cytotoxicity, enable easy modification of their surfaces, have straightforward synthesis processes and excellent biocompatibility [8][9][10]. Such advantages make metallic NPs obtained by green synthesis (gNPs) prospective for applications in biological analysis, drug delivery and imaging, environmental monitoring, industrial catalysis and electronic devices [11][12][13][14][15][16][17][18][19]. A special role of these gNPs is related to antimicrobial and antibiofilm agents [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Various physical and chemical process like laser radiation [8], sonochemical method [9], co-precipitation [10], inverse microemulsions [11], ultrasound irradiation [12], and chemical reduction [13] have been reported for the synthesis of metal nanoparticles. All these methods require dangerous chemicals, noxious solvents, high temperature and pressure conditions, and so on [14][15][16]. However, biological methods are very simple, eco-friendly, and do not require toxic reducing and stabilising agents, therefore this method is widely used [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Au-NPs were synthesised from HAuCl 4 using a papaya leaf extract via a green synthetic technique. Investigating these NPs for biomedical applications revealed that they are effective against S. aureus and P. putida (Sunkari et al, 2017).…”
Section: Plant Extract Encapsulated With Mnpsmentioning
confidence: 99%